Internal Public Sector Contro - Boudjelka, Laid (جامعة الوادي University of Eloued, 2025)
Because managers are aware of how challenging it will be to maintain effective internal control over legacy systems while minimizing unexpected events, managers always strive to improve internal controls in their businesses. Internal controls, on the other hand, will be necessary to improve productivity, reduce asset loss, achieve a reasonable assurance of the accuracy of financial statements, and comply with laws and regulations. Internal public sector control plays a pivotal role in ensuring transparency, accountability, and the efficient management of public resources. This paper reviews the key frameworks guiding internal controls, with a primary focus on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) and the International Organization of Supreme Audit Institutions (INTOSAI). These globally recognized frameworks provide structured approaches to governance by emphasizing critical components such as control environments, risk assessment, monitoring, and compliance. They serve as foundational tools for achieving organizational objectives and mitigating risks, particularly in public administration. While the adoption of these frameworks has yielded significant benefits, including enhanced financial oversight, fraud prevention, and public trust, the study identifies persistent challenges that undermine their effectiveness. These include limited financial and human resources, technological gaps, political interference, and resistance to change within organizations. These barriers are particularly pronounced in developing countries, where resource constraints and weak governance structures exacerbate implementation difficulties. This paper also explores emerging opportunities for strengthening internal controls through innovation and reform. Advanced technologies, such as artificial intelligence and blockchain, present transformative potential for improving real-time monitoring, automating risk assessments, and ensuring data integrity. Additionally, capacity-building initiatives, independent audits, and policy reforms are essential to addressing existing gaps and enhancing the independence and reliability of control systems. By analysing these frameworks, their challenges, and future opportunities, this paper underscores the critical role of internal controls as a dynamic tool for fostering transparency and accountability in public administration. The study concludes with actionable recommendations for aligning control systems with international standards, investing in technology, and fostering a culture of accountability. These reforms are necessary for governments to optimize resource management, enhance trust, and ensure sustainable governance outcomes.
Internal Public Sector Control: A Review of Frameworks for Effective Governance
Keywords: Internal Public Sector Control; Governance; Accountability; Transparency; COSO Framework; INTOSAI Framework; Risk Management